The back in the swing cookbook : recipes for eating and living well every day after breast cancer - Unell, Barbara C., 1951- (Andrews McMeel Pub., 2012)
A life-affirming book full of 150 feel-good recipes that are easy to prepare, with fresh ingredients specifically designed to help breast cancer survivors get back in the swing of joyful, healthy living--